Philoxenia, a Social Performative Practice? - Volanakis, Adonis (My University, 2015)
What makes performative writing in the space of a page look like a dancer/philosopher in the streets? Why is space the vital condition of dramaturgy in the contemporary discourse of both visual and performing arts? How are scenography and its derivatives the pivot points for reexamining spectatorship? This article started as a performative lecture at the International Colloquium “Qu’est-ce que la scénographie?” held on 21–22 October 2011 in Paris,1 which was then published in French as “La scénographie, une pratique sociale performative?” (2012).2 After a number of fruitful discussions with Randy Martin, the article evolved into the present English version, opening for me new paths into space and performativity. Shared space: a bridge-maker between aesthetics and politics, visual and performing arts, theatre and dance, and, above all, human relationships. Philoxenia: the situation where the xenos (ξένος), the stranger, becomes a philos (φίλος), a friend. Is art able to build space for hospitality and movement for the viewer, witness, participant, spectator, co-author and co-producer of meaning?
Keywords: Scenography; Spatial; Performative; Dance; Theatre; Spectatorship; Social practice